1985
DOI: 10.1128/jvi.54.2.337-344.1985
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of African swine fever virus

Abstract: We describe a method for African swine fever (ASF) virus purification based on equilibrium centrifugation in Percoll density gradients of extracellular virions produced in infected VERO cells that yielded about 15 +/- 9% recovery of the starting infectious virus particles. The purified virus preparations were essentially free of a host membrane fraction (vesicles) that could not be separated from the virus by previously described purification methods. The purified virus sedimented as a single component in sucr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(77 citation statements)
references
References 35 publications
(26 reference statements)
2
75
0
Order By: Relevance
“…This is supported in part by an electron microscopic examination of macrophages which reveals that SLA Class I and Class II molecules are associated with internal ASF viral particles detected by mAb and immunogold staining (M. Gonzalez Juarrero et al, unpublished data, 1988 ). As these viral particles bud from the macrophage surface at later times in the infection, they may carry these SLA proteins in the viral envelope, similar to the earlier report of ASFV budding from Vero cells (Carrascosa et al, 1985). A decrease in expression of SLA Class II may lead to a decrease in antigen presentation, a mechanism favorable for survival of the virus.…”
Section: Discussionsupporting
confidence: 79%
“…This is supported in part by an electron microscopic examination of macrophages which reveals that SLA Class I and Class II molecules are associated with internal ASF viral particles detected by mAb and immunogold staining (M. Gonzalez Juarrero et al, unpublished data, 1988 ). As these viral particles bud from the macrophage surface at later times in the infection, they may carry these SLA proteins in the viral envelope, similar to the earlier report of ASFV budding from Vero cells (Carrascosa et al, 1985). A decrease in expression of SLA Class II may lead to a decrease in antigen presentation, a mechanism favorable for survival of the virus.…”
Section: Discussionsupporting
confidence: 79%
“…This finding raised the possibility that these vesicles could contain virus particles. Previous publications reported that the abundant vesicle fraction released in last ASFV infection stages contains virus (Carrascosa et al, 1985). Then, it is conceivable that the fluorescence detected in the vesicles formed at the end of apoptosis (blebbing), could correspond to GFP labeled virus particles.…”
Section: Discussionmentioning
confidence: 97%
“…In most cases, ASFV stocks from culture supernatants were semipurified from vesicles by ultracentrifugation at 40.000 × g through a 20% (w/v) sucrose cushion in PBS for 1 h at 4°C. When needed, ASFV particles were highly purified from the extracellular medium by Percoll equilibrium centrifugation as previously described (Carrascosa et al, 1985). After centrifugation, Percoll gradients were fractionated and fractions 2 to 8 from Percoll gradients, containing virus particle essentially free of vesicles and contaminant membranes, were collected after sedimentation and gel filtered through Sephacryl S-1000 (Amersham) to remove Percoll.…”
Section: Cells Viruses and Plasmidsmentioning
confidence: 99%
“…The ASFV strain BA71V, adapted to grow in Vero cells, has been previously described (Enjuanes et al, 1976). Highly purified ASFV was obtained by Percoll equilibrium centrifugation as described by Carrascosa et al (1985).…”
Section: Cells and Virusesmentioning
confidence: 99%